Aqsam Al-Qur’an - Zikri, Abdalul; Ondeng, Syarifuddin; Shahib, Muhammad Amin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study shows that an oath is a commitment to the soul not to do something or to do it, which is strengthened by something that is glorified by the person who swears, either in reality or just by belief. The pillars in the aqsam of the Koran are fi'il qasam, muqsam bih and muqsam alaih. The letters used in the aqsam are the first letter wau and the letter ba'. Oaths that use the letter wau do not need to use the pronunciation aqsama, ahlafa. An oath that uses the letter ba' can be accompanied by words indicating an oath or may not include an oath. There are forms of aqsam in the Koran that use the original form, plus the letter La, plus the words Qul Bala, plus the words Qul Iiy This aqsam from the Koran functions as an amplifier (ta'kid) speech so that the listener can easily be accepted and trusted. In qasam there are also benefits, including the news has reached the listener, and he is not the person who a priori, the news has been accepted and believed because it has been strengthened by an oath. The preacher of the news has felt relieved, because he has conquered the listener by strengthening the news with an oath.